Recycling Of Construction Waste: Awareness and Constraints among Contractors in Sarawak - Nur Sharfina, Muhammad Shukri; Nik Fatma Arisya, Nik Yahya; Masidah, Abdul Majid (2016)
Construction debris such as woods, drywall, metals, cupboard, masonry and others (i.e. Portland cement concrete, asphalt concrete, asphalt, shingles, plastic, glass and soil) are the common waste material that results from the construction, renovation or demolition of structures such as bridges, roads and buildings. Due to vast quantity of construction wastewhenever there is a construction activity, there is a need to minimize the quantum in order to protect the environment. One of the methods is through recycle. Recycle has been part of the environmental considerations but has yet to be widely practice in the construction industry of Malaysia. Due to the urgency to minimize construction waste, there is a need to identify what are the constraints to implement recycling method. İt is also important to first determine the level of awareness among the contractors in adopting the method. Questionnaire were distributed and collected from 36 respondents from contracting companies in Sarawak through online survey. Overall findings of the research shows that most of the respondents agree that it is important to implement recycle construction waste material as the method reduces the demand upon new resources as well as cutting down the cost and effort of transportation and production. However there are some barriers in implementing recycle method such as lack of appropriate recycling facilities centre, the quality of construction waste is not up to the standard to be recycledand the quantity of wastes are huge. Hence, immediate reaction needs to be planned by the government in close cooperation with the key players.